The humanities and the understanding of reality - Stroup, Thomas B. (Thomas Bradley), 1903-1992 (University of Kentucky Press, 1966)
In their concern with the perennial controversy between the two great areas in which men seek knowledge, three eminent literary scholars and a distinguished journalist in these essays address themselves to the question, ""Do the humanities provide a form of understanding of reality that the sciences do not?""Monroe C. Beardsley maintains that the humanities considered as contributors to knowledge must deal with the same subject matter as the sciences, but literature and the arts can enlarge our powers of understanding human nature, although not in the way the sciences do (under empirically or.